Extremism, radicalization and security : an identity theory approach - Richards, Julian (Palgrave Macmillan, 2020)
Contents: Introduction -- Section I. Identity, extremism, radicalization, terrorism -- Intersections between identity and security -- Radicalization, extremism, terrorism -- Reactive identity movements -- Section II. State, society, narrative, political myth -- Political myth and discourse analysis in security -- Identity and security narratives in contemporary Britain -- State policy and strategy: prevent, "multi-agency" responses, and the way forward -- Conclusions.